2013
DOI: 10.1523/jneurosci.1327-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26b, Upregulated in Alzheimer's Disease, Activates Cell Cycle Entry, Tau-Phosphorylation, and Apoptosis in Postmitotic Neurons

Abstract: MicroRNA (miRNA) functions in the pathogenesis of major neurodegenerative diseases such as Alzheimer's disease (AD) are only beginning to emerge. We have observed significantly elevated levels of a specific miRNA, miR-26b, in the defined pathological areas of human postmortem brains, starting from early stages of AD (Braak III). Ectopic overexpression of miR-26b in rat primary postmitotic neurons led to the DNA replication and aberrant cell cycle entry (CCE) and, in parallel, increased tau-phosphorylation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
186
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(189 citation statements)
references
References 83 publications
3
186
0
Order By: Relevance
“…29 Activation of E2F1-mediated transcription in neurons upon injury, AD and PD has been reported before and has been associated to neuronal damage. 9,45,46 In our study, we observe that upon KA, the Ccnd1/Rb/E2F1 axis is positively regulated leading to an increase in transcription of PCNA and Cyclin E1 in neurons. Such regulation was absent in the RBPJKcKOs.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…29 Activation of E2F1-mediated transcription in neurons upon injury, AD and PD has been reported before and has been associated to neuronal damage. 9,45,46 In our study, we observe that upon KA, the Ccnd1/Rb/E2F1 axis is positively regulated leading to an increase in transcription of PCNA and Cyclin E1 in neurons. Such regulation was absent in the RBPJKcKOs.…”
Section: Discussionsupporting
confidence: 50%
“…[3][4][5][6] Recent studies have proposed some important molecular players involved in CCR in neurons. [7][8][9][10] Yet, a precise molecular pathway triggered by diverse neurodegenerative stimuli that leads to CCR in neurons remains unidentified.…”
mentioning
confidence: 99%
“…Recently, several miRNAs have been found to be related to AD pathogenesis by affecting the expression of function of AD-relevant molecules such as amyloid precursor protein (APP) (7), β-site amyloid precursor protein cleaving enzyme 1 (BACE1) (8) or Tau (9,10). Measurements of miRNAs in blood and cerebrospinal fluid (CSF) have become a novel diagnostic tool for various neurological diseases, including AD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xu et al (2008) demonstrated that miR124a ectopic expression decreases dendritic branching, an effect rescued by the loss of dFMRP expression. In addition, miRNAs in circulating blood are candidate biomarkers for early phases of neurological disease De Smaele et al 2010;Absalon et al 2013). Moreover, miRNAs may offer promise as therapeutics for disease states using multiple approaches (Sayed and Abdellatif 2011;Im and Kenny 2012).…”
mentioning
confidence: 99%